Globalizacja a trendy ewolucji funkcji personalnej - Antczak, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author presents the results of scientific research and diagnosis of the evolution of personnel function (HRM, Human Resources Management) in enterprises functioning in Polish conditions in the circumstances of globalizing Polish economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 235-243